Fractured, altered, and faulted basement in northeastern Oklahoma: Implications for induced seismicity. (June 2021) - Hamilton, M.; Carpenter, B.; Johnston, C.; Kolawole, F.; Evans, S.; Elmore, R.D.
Abstract: Due to a decade of wastewater injection-triggered seismicity, the crystalline basement of northern Oklahoma has become the subject of intensive research, almost all of which has relied upon remote sensing or analog models and materials due to a near total absence of outcrops. This study reports relevant characteristics of material in drill cores from the area, the best available analog for seismogenic northern Oklahoma basement. Fractures are present in all cores, remain abundant over 100 m below the top of basement, commonly have steep inclinations (≥70°) and are nearly universally mineralized. Many fractures show evidence of slip such as slickenlines, vein offset, brecciation, and in one core injectite formation. Fractures are mineralized by carbonates and/or phyllosilicates along with various other minerals, some contain vugs, and many contain multiple generations of minerals. Color changes suggestive of redox processes, including possible paleoweathering, are associated with fractures and proximity to the basement unconformity. Paragenesis of fracture minerals and variations in geochemical analyses of altered rocks indicate complex histories of deformation and fluid activity. The abundance of fractures in cores indicates that the upper basement of northeastern Oklahoma is much less "intact" than commonly assumed; it instead shows similarities to fractured basement plays, which may provide a more reasonable comparison for future work.